On correction of full-scale test data obtained during sea trials in ice conditions - A. S. Makarov; A. A. Trunin; А. С. Макаров; А. А. Трунин (Arctic and Antarctic Research, 2016)
The problem of ﬂ uctuations of the sea-level in the Arctic zone of Russian Federation in during Holocene. Based on the analysis of more than 600 dating of documents testifying to the level position of the Russian Arctic seas during the Holocene using principal component analysis was able to identify paleo-events of the high standing of the sea level during the Holocene in time periods 6000, 4000 and 2500–1500 y.b.p. and to identify possible reasons for such changes. Рассматривается проблема изменчивости уровня морей арктической зоны Российской Федерации в голоцене. На основании анализа более чем 600 датировок документов, свидетельствующих о положении уровня морей АЗРФ в голоцене с использованием метода главных компонент удалось выявить палеособытия повышенного стояния уровня этих морей в голоцене на этапах 6, 4 и 2,5–1,5 тыс.л.н. и определить возможные причины таких изменений.